Feed conversion and seed survival of Nile tilapia (Oreochromis. niloticus Linnaeus, 1758) feed by recombinant growth hormone through immersion and feed - Nurul Azzahra Lukman; Andi Aliah Hidayani; Asmi Citra Malina; Alimuddin Alimuddin; Muhammad Fuadi (Jurnal Iktiologi Indonesia, 2022)
Tilapia (Oreochromis niloticus) is one of the freshwater fish that is of great interest to the public, because its protein content is quite high, namely 55.58%. One of the problems in tilapia cultivation is that the need for feed is very high, where only 25% of the feed given is converted as a result of production and the rest is wasted as waste. This greatly affects the costs in the cultivation business. One alternative to overcome this problem is the use of Recombinant Growth Hormone (rGH). This study aimed to evaluate the effect of rGH administration on feed conversion ratio and survival of Tilapia (O. niloticus) given rGH through a combination method of submersion and feed rGH (oral boosting). The test animals used tilapia seeds with a size of 2-3 cm with 40 days of maintenance. A plastic jar with a volume of 10 L filled with 8 L of water and stocking density of 40 tilapia seeds. Test animals were given feed commercial made feed at a dose of 5% of body weight. This study used a completely randomized design (RAL) consisting of 4 treatments with 3 replications each, namely A (control), B (submersio), C (feed rGH oral boosting), and D (submersio+feed rGH oral boosting). The results showed that the effect of rGH administration gave the best results in treatment D, submersion+ feed rGH (oral boosting), the ratio feed conversion (FCR) was (0.77 ± 0.02) and survival rate was 92.50%. Provision of rGH through the combination method of submersion + feed rGH (oral boosting) can increase the efficiency of good utilization and high survival. Abstrak Recombinant Growth Hormone (rGH) merupakan salah satu metode alternatif untuk mengatasi masalah pertumbuhan dan tingginya kebutuhan pakan dalam budidaya ikan nila. Penelitian ini bertujuan untuk mengevaluasi pertumbuhan, nisbah konversi pakan dan sintasan benih ikan nila (O. niloticus) yang diberikan rGH melalui metode kombinasi perendaman dan pakan buatan. Ikan uji yang digunakan yaitu benih ikan nila ukuran 2-3 cm sebanyak 480 ekor dengan lama pemeliharaan 40 hari. Ikan dipelihara pada wadah plastik bening dengan volume 10 L yang diisi air sebanyak 8 L dengan padat tebar 40 ekor setiap wadahnya. Ikan diberi pakan buatan dengan dosis 5% dari bobot tubuh. Penelitian ini menggunakan rancangan acak lengkap yang terdiri atas 4 perlakuan dengan masing-masing 3 ulangan, yaitu A (kontrol), B (perendaman), C (pakan), dan D (kombinasi perendaman + pakan). Aplikasi rGH ke pakan buatan komersil dengan dosis 30 mL rGH dalam satu kg pakan, sementara untuk perendaman dengan dosis 100 mL larutan rGH untuk 120 ekor ikan dalam 10 L air. Hasil penelitian menunjukkan bahwa perlakuan perendaman + pakan rGH memberikan hasil yang terbaik, yaitu pertumbuhan spesifik sebesar 5,29 %/hari, nisbah konversi pakan sebesar (0,77 ± 0,02) dan sintasan 92,50%. Pemberian rGH dengan kombinasi perendaman dan oral berpotensi dalam meningkatkan produktivitas dan efisiensi biaya dalam budidaya ikan nila.